Characterization of Pseudomonas aeruginosa Quorum Sensing Inhibitors from the Endophyte Lasiodiplodia venezuelensis and Evaluation of Their Antivirulence Effects by Metabolomics - Léonie Pellissier (Microorganisms, 2021)
The opportunistic pathogen Pseudomonas aeruginosa is one of the “critical priority pathogens” due to its multidrug resistance to a wide range of antibiotics. Its ability to invade and damage host tissues is due to the use of quorum sensing (QS) to collectively produce a plethora of virulence factors. Inhibition of QS is an attractive strategy for new antimicrobial agents because it disrupts the initial events of infection without killing the pathogen. Highly diverse microorganisms as endophytes represent an under-explored source of bioactive natural products, offering opportunities for the discovery of novel QS inhibitors (QSI). In the present work, the objective was to explore selective QSIs within a unique collection of fungal endophytes isolated from the tropical palm Astrocaryum sciophilum. The fungi were cultured, extracted, and screened for their antibacterial and specific anti-QS activities against P. aeruginosa. The endophytic strain Lasiodiplodia venezuelensis was prioritized for scaled-up fractionation for its selective activity, leading to the isolation of eight compounds in a single step. Among them, two pyran-derivatives were found to be responsible for the QSI activity, with an effect on some QS-regulated virulence factors. Additional non-targeted metabolomic studies on P. aeruginosa documented their effects on the production of various virulence-related metabolites.